2018 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM) 2018
DOI: 10.1109/speedam.2018.8445212
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Modulation Techniques for Modular Multilevel Converters in Traction Drives

Abstract: The spreading of electric vehicles led to a renewed interest for innovative traction drives. In this context, an electric traction drive based on a Modular Multilevel Converter and integrating batteries in each module has been recently proposed. This converter concentrates into a single unit, the control of the traction motors, the balancing and energy management of the battery cells and the vehicle recharge functions. By using different modulation techniques it is possible to optimize different aspects like e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The number of levels in series to activate is then determined in real-time by rounding up to the nearest integer the real value given by a closed-loop control. The use of NLC for SRB driving has been compared with carrier cascaded PWM in [18]. It was shown that PWM control patterns tend to have a better THD when a low number of levels in series is used, while NLC induces less loss due to the reduced amount of commutations.…”
Section: Srb Fundamentalsmentioning
confidence: 99%
“…The number of levels in series to activate is then determined in real-time by rounding up to the nearest integer the real value given by a closed-loop control. The use of NLC for SRB driving has been compared with carrier cascaded PWM in [18]. It was shown that PWM control patterns tend to have a better THD when a low number of levels in series is used, while NLC induces less loss due to the reduced amount of commutations.…”
Section: Srb Fundamentalsmentioning
confidence: 99%
“…LLPWM is an hybrid NLC-PWM modulation strategy proposed in [24]. LLPWM generally activates the components of the converter using NLC.…”
Section: F Last Level Pwm (Llpwm)mentioning
confidence: 99%
“…The W-PWM enables a precise control of the PWM window and the length of this window is effectively a new degree of freedom for the control system. It is worth noting that for certain values of φ that depends on the number of modules of the converter and on the magnitude of the voltage reference, W-PWM reduces to LLPWM modulation [24].…”
Section: Windowed Pwm (W-pwm)mentioning
confidence: 99%
“…In literature different modulation techniques for this converter topology are available. The modulation techniques can be divided in two categories: nearest level control technique (NLC) and pulse width modulation (PWM) based ones [14]. NLC approximates the output voltage by turning on and off modules in order to minimize the discretization error related to the voltages of the modules, while PWM techniques add a switching signal to the output of NLC.…”
Section: Converter Controlmentioning
confidence: 99%